INVARIANT RANDOM APPROXIMATION IN NONCONVEX DOMAIN - Shrivastava, R.; Nashine, H. K.; Dewangan, C. L. (IndoMS, 2009)
Random fixed point results in the setup of compact and weakly compact domain of Banach spaces which is not necessary starshaped have been obtained in the present work. Invariant random approximation results have also been determined asits application. In this way, random version of invariant approximation results due toMukherjee and Som [13] and Singh [17] have been given.DOI :Â http://dx.doi.org/10.22342/jims.15.2.45.69-77